Beyond Ethnography and Beneath the Bedrock Mortars: The Eastern Transverse Ranges of Southern California as Early Holocene Refugia. (2nd January 2022) - Allen, Mark W.; Sapp, William; Rogers, Alexander K.; James, Steven R.; Acebo, Nathan
ABSTRACT: Rock Camp (CA-SBR-342) in the San Bernardino Mountains has been regarded as a seasonal Late Prehistoric Complex acorn processing base camp since it was excavated in the 1960s. Reanalysis of its collections and new investigations at the nearby Willow Creek Crossing sites permit reevaluation of archaeological models for the Transverse Ranges of southern California and the adjacent Mojave Desert. Diagnostic artifacts, site structure, and obsidian hydration dating indicate montane Greven Knoll I (9, 400-4, 000 BP) occupations in inland southern California several millennia earlier than has been previously posited. Moreover, the presence of stemmed points suggests that the Greven Knoll Pattern of the Encinitas Tradition was introduced into the region directly from the Mojave Desert during the onset of the Altithermal. This analysis also serves as a reminder for archaeologists to use ethnohistoric models with caution and to look beyond the obvious.